Transitioning out of elite sport: The central role of groups in support experiences - Crook, R.; Coffee, P.; Bank, C.; Neely, K. C.; Hartley, C.; Haslam, C.; Tamminen, K. A. (Psychology of Sport and Exercise, 2025)
In the present study, we explored the perceived impact of changes in athletes' social group memberships on their identities and social support experienced during transition to retirement. Using interpretative phenomenological analysis, we explored how athletes interpreted their experiences and connected them to their personal and social environments. Participants were seven (5 male, 2 female) former elite athletes, aged 26 and 40 years (Mage = 34 ± 4.96 years). They represented badminton, basketball, football/soccer, and rugby, having transitioned from their sport careers 9 months to 11 years prior to data collection (M = 5.25 ± 3.85 years). Data were collected through semi-structured interviews, and analysis included reflexivity and an independent audit trail. We identified four main themes: (a) support received from maintaining existing social groups, (b) support opportunities gained by joining new social groups, (c) the support lost through identity changes in retirement, and finally, (d) the support offered by adopting a retired athlete identity. The results highlight the importance of approaching athlete identity and retirement from a social identity perspective. Our results also suggest that social groups and subsequent social identities may influence psychosocial outcomes through group-based social support, while arguing that the effectiveness of social support depends on the compatibility of these identities with an athlete's existing or gained identities. Finally, we offer applied considerations for athletes and sport organizations, suggesting that retired athletes benefit from mentoring and engaging in organizations supporting transitioned athletes to build meaningful connections during this transition.